Germany’s Colonial Policy in Contemporary German Social and Political Discourse - A. P. Sokolov; A. D. Davydov (Международная аналитика, 2022)
The intensification of the discussion on the German colonial past at the present stage combines the experience of historical research on this topic with the domestic and foreign policy objectives of Germany’s leadership. The purpose of this article is to examine the process of rethinking the colonial past in the Federal Republic of Germany as a part of ideological support for the FRG’s foreign policy on the African direction. The article examines how the debate over Germany’s colonial past has evolved in recent years, and how the intensification of the debate affects the government’s policy towards African countries. The conclusion is that Berlin’s address to this topic so far rarely goes beyond academic and socio-political debate, while the tangible steps of the government remain mostly at the level of declarative intentions. While expressing willingness to admit responsibility for the destruction wrought, the authorities of the Federal Republic of Germany seek to maintain control over its “monetization,” as they fear to get a flow of bills with potentially unlimited sums. Most initiatives are in the first stages of implementation and far from meeting the requests of African states. Germany’s colonial history, marked by both crimes against the local population and the infrastructure development of its controlled territories, is a potential resource for engagement with African countries. The importance of Africa for German foreign policy as expected will increase in the future due to economic, demographic and geopolitical factors.